2015
DOI: 10.1109/tvt.2014.2371531
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized 3-D Scattering Channel Model for Spatiotemporal Statistics in Mobile-to-Mobile Communication Environment

Abstract: In this paper, we develop a three-dimensional geometrical channel model for mobile-to-mobile (M2M) communication environment. The proposed model combines most of the existing two-dimensional (2D) and three-dimensional (3D) geometrical channel models for M2M and fixed-to-mobile (F2M) communication channels into one generalized model. Using the proposed model, closed-form expressions for the joint probability density function (PDF) of angle-of-arrival (AoA) and time-ofarrival (ToA) in azimuth and elevation plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…This is because the clipped scattering region is geometrically asymmetric, as illustrated in Figs. 3 and 4, and the number of multi-path components corresponding to the positive and negative Doppler frequencies is unequal [12]. Moreover, it is observed that the PDFs of Doppler frequency gradually increase with an increase in the distance between the MT and MR or the number of reflections.…”
Section: B Distribution Of the Doppler Frequencymentioning
confidence: 96%
See 3 more Smart Citations
“…This is because the clipped scattering region is geometrically asymmetric, as illustrated in Figs. 3 and 4, and the number of multi-path components corresponding to the positive and negative Doppler frequencies is unequal [12]. Moreover, it is observed that the PDFs of Doppler frequency gradually increase with an increase in the distance between the MT and MR or the number of reflections.…”
Section: B Distribution Of the Doppler Frequencymentioning
confidence: 96%
“…In general, the transmission signal from the MT to the MR under multi-bounced propagation paths. However, for the conventional scattering channel models in [5][6][7][8][9][10][11][12][13], they almost concentrated on the single-and doublebounced models. For this we should propose multi-bounced scattering channel model, which can be utilized to accurately describe mobile radio communication environments.…”
Section: A Virtual Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In V2V communication channels, both the transmitter (Tx) and the receiver (Rx) may be in motion and lower than scatterers on surrounding buildings, which is different from conventional fixed-to-mobile (F2M) cellular systems. The performance of V2V propagation channel between Tx and Rx can significantly differ depending on scattering environments around them and whether the link exists line-of-sight (LoS) components owing to buildings, roadside infrastructures, and road bending [4]. V2V channels generally may have contributions from LoS paths, reflections from large stationary and moving objects such as buildings and neighboring vehicles, and a diffuse base from large numbers of small stationary objects in the environment.…”
Section: Introductionmentioning
confidence: 99%